Protocol of the digital long COVID study: A single-center, registry-based, feasibility and clinical evaluation study to investigate a 12-week digital intervention program for people affected by post-COVID-19 condition - Stefan Rohner; Rebekka Schnepper; Andrea Meienberg; Katrin Bopp; Michael Mayr; Gunther Meinlschmidt; Rainer Schaefert (PLoS ONE, 2026)
Up to 400 million individuals globally are estimated to experience persistent symptoms, including fatigue, muscle pain, and brain fog, following severe acute respiratory syndrome coronavirus type 2 infection. These persistent symptoms are referred to as Post-COVID-19 condition if they last for more than 12 weeks after infection and persist for at least 8 weeks and often causing significant distress and burden. The underlying pathological mechanisms have not yet been fully elucidated. Due to the heterogeneity of the disease a multifactorial origin is highly likely. Overall, evidence on optimal management is limited, and no medication has yet proven to be effective. Current symptom management and treatment guidelines suggest a biopsychosocial perspective and emphasize multidisciplinary approaches. Comprehensive interventions, adequate treatment access, and appropriate resources remain insufficiently available and implementing digital interventions might help mitigate these limitations. This protocol details a single-site feasibility and clinical evaluation study aiming to bridge this gap. By implementing an exploratory, open-label, digital interventional approach this study investigates the feasibility and efficacy of a 12-week program delivered by a cloud-based application. The program consists of 13 modules encompassing a wide range of topics (e.g., energy management, self-care, stress management) and includes informational (e.g., psychoeducational content) and interactive (e.g., exercises, self-reflection diaries) components. Customization options align the material with participant needs. A dedicated feedback section in each module captures feedback regarding usability and feasibility. Participants are monitored and checked for adherence throughout the study. The primary outcome is the post-intervention change in functional capacity measured by the World Health Organization Disability Assessment Schedule 2.0. All participants provide written informed consent. Key results from the study will be published in peer-reviewed journals.